Interrogating the text: questioning to mediate junior secondary school students’ barriers to reading comprehension - Sholihatul Hamidah Daulay; Achmad Ramadhan; Adelia Fitriani (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
Reading comprehension is the capacity to analyze and comprehend the text’s meaning. Reading through questioning techniques can improve the skill of thinking, but it can also be a problem for some individuals. This study aims to unveil EFL students’ barriers in reading comprehension through questioning technique. Eight students and one English teacher at a private junior secondary school in Medan, South Sumatera, Indonesia participated in this study. Nested in qualitative descriptive method, classroom observation and semi-structured interview were used to gather data. Study findings expose that the researchers found the students’ problems in reading comprehension through questioning techniques, such as problems in concentration, problems in understanding vocabulary, comprehending long sentences, arranging words in English, applying grammatical rules, and understanding how to pronounce the words (error pronunciation). In response to the students’ barriers, this study recommends to solve these problems through organizing an ice-breaking, giving some questions to students, and providing opportunities for students to ask questions.